Schistosome infection aggravates HCV‐related liver disease and induces changes in the regulatory T‐cell phenotype. (February 2015) - Loffredo‐Verde, E.; Abdel‐Aziz, I.; Albrecht, J.; El‐Guindy, N.; Yacob, M.; Solieman, A.; Protzer, U.; Busch, D. H.; Layland, L. E.; Prazeres da Costa, C. U.
Summary Schistosome infections are renowned for their ability to induce regulatory networks such as regulatory T cells (Treg) that control immune responses against homologous and heterologous antigens such as allergies. However, in the case of co‐infections with hepatitis C virus (HCV), schistosomes accentuate disease progression and we hypothesized that expanding schistosome‐induced Treg populations change their phenotype and could thereby suppress beneficial anti‐HCV responses. We therefore analysed effector T cells and n/iTreg subsets applying the markers Granzyme B (GrzB) and Helios in Egyptian cohorts of HCV mono‐infected (HCV), schistosome‐co‐infected (Sm/HCV) and infection‐free individuals. Interestingly, viral load and liver transaminases were significantly elevated in Sm/HCV individuals when compared to HCV patients. Moreover, overall Treg frequencies and HeliosposTreg were not elevated in Sm/HCV individuals, but frequencies of GrzB+Treg were significantly increased. Simultaneously, GrzB+ CD8+ T cells were not suppressed in co‐infected individuals. This study demonstrates that in Sm/HCV co‐infected cohorts, liver disease is aggravated with enhanced virus replication and Treg do not expand but rather change their phenotype with GrzB possibly being a more reliable marker than Helios for iTreg. Therefore, curing concurrent schistosome disease could be an important prerequisite for successful HCV treatment as co‐infected individuals respond poorly to interferon therapy.